Diversity of Macrozoobenthos as Bioindiactor for Water Quality of Jangkok River Lombok Island - Yusrianti, Rosita; Khairuddin; Japa, Lalu (Jurnal Biologi Tropis, 2024)
Macrozoobenthos are aquatic organisms that can be as bioindicators of water quality. Species diversity of macrozoobenthos communities plays an important role in assessing water quality. This research was conducted in Desember 2023 to analyze the level of diversity of macrozoobenthic species and the water quality of the Jangkok River, Lombok Island. Sampling stations representing the Upstream (Sesaot Village, Narmada District), Centralstream (Sayang-sayang Village, Cakranegara District) and Downstream (Dasan Agung, Mataram City) of Jangkok River. The results of this research showed that macrozoobenthos community in the waters of Jangkok River consisted of 14 species members of 5 clases. Four species with highest abundance ware Corbicula Fluminea, Gerris remingis, Pomacea canaliculata and Solenocera sp. from clases of Bivalvia, Insecta, Gastropoda, and Crustacea, respectively. Species diversity index of macrozoobenthos in the Jangkok River was 2.4, indicated that water of Jangkok River was not in pollution. However, the river remains vulnerable to pollution, both at light and moderate levels.